Concerns about conclusions of the POLAR trial: reply - Michel, Laura L.; Müller, Jana; Weiler, Markus (JAMA oncology, 2025)
In Reply We thank Ventzel and colleagues for their thoughtful commentary on our recent article. While we respectfully disagree with several of the points raised, we appreciate the opportunity to address these concerns and clarify aspects of our methodology and interpretation.Chemotherapy-induced peripheral neuropathy (CIPN) can affect both the feet and hands, leading to distinct functional impairments and different types of interference with daily activities and health-related quality of life (QoL). Whereas symptoms in the feet typically affect balance and walking, symptoms in the hands more commonly affect fine motor skills. To our knowledge, there is no evidence suggesting that symptoms in the feet have a greater (or lesser) affect on activities of daily living or QoL. This is likely highly individual depending on factors such as profession (eg, mail carrier vs jewelry maker) or leisure activities (eg, runner vs harpist).
Gesehen am 02.12.2025